Spatial notion in 5-year-old children from a Public Educational Institution and a Private Educational Institution - Alanya Quesada, Stefany Marisol (2019)
The main objective of the research was to determine the differences in the spatial notion in 5-year old children of a public educational institution and a private educational institution. The study refers to the notions of space in the framework of a constructive and relational process with its environment. It is a quantitative methodology, non-experimental design, comparative and transactional descriptive level. We worked with a sample of 105 5-year-old children using an observation guide as a data collection instrument that was duly validated and has high reliability. After data collection and statistical analysis, it is concluded that there are differences in the spatial notion in 5-year-old children of a Public Educational Institution and a Private Educational Institution, Lima - 2019. With a value of significance <0.005 according to the U-test. Mann Whitney.